TNFα sensitizes hepatocytes to FasL-induced apoptosis by NF[kappa]B-mediated Fas upregulation - Faletti, Laura; Peintner, Lukas; Neumann, Simon; Sandler, Sandra; Grabinger, Thomas; MacNelly, Sabine; Merfort, Irmgard; Huang, Chun-Hao; Tschaharganeh, Darjus-Felix; Kang, Tae-Won; Heinzmann, Florian; D’Artista, Luana; et al. (Cell death & disease, 2018)
Although it is well established that TNFα contributes to hepatitis, liver failure and associated hepatocarcinogenesis via the regulation of inflammation, its pro-apoptotic role in the liver has remained enigmatic. On its own, TNFα is unable to trigger apoptosis. However, when combined with the transcriptional inhibitor GaLN, it can cause hepatocyte apoptosis and liver failure in mice. Moreover, along with others, we have shown that TNFα is capable of sensitizing cells to FasL- or drug-induced cell death via c-Jun N-terminal kinase (JNK) activation and phosphorylation/activation of the BH3-only protein Bim. In this context, TNFα could exacerbate hepatocyte cell death during simultaneous inflammatory and T-cell-mediated immune responses in the liver. Here we show that TNFα sensitizes primary hepatocytes, established hepatocyte cell lines and mouse embryo fibroblasts to FasL-induced apoptosis by the transcriptional induction and higher surface expression of Fas via the NFκB pathway. Genetic deletion, diminished expression or dominant-negative inhibition of the NFκB subunit p65 resulted in lower Fas expression and inhibited TNFα-induced Fas upregulation and sensitization to FasL-induced cell death. By hydrodynamic injection of p65 shRNA into the tail vein of mice, we confirm that Fas upregulation by TNFα is also NFκB-mediated in the liver. In conclusion, TNFα sensitization of FasL-induced apoptosis in the liver proceeds via two parallel signaling pathways, activation of JNK and Bim phosphorylation and NFκB-mediated Fas upregulation.
Im Titel ist [kappa] als griechischer Buchstabe dargestellt
Gesehen am 16.04.2020